ANALISA EFEKTIVITAS ALAT PENUKAR KALOR JENIS SHELL AND TUBE HASIL PERENCANAAN MAHASISWA SKALA LABORATORIUM - Saut Siagian (Bina Teknika, 2016)
Heat exchanger is a means of heat transfer from the fluid temperature is higher to a fluid othertemperature is lower, in which the heat exchanger is one tool that is often found in industries suchas thermal power plant, machinery chemical processes, equipment air conditioner, refrigerator,radiators etc. The design of the exchanger draw string shell and tube is planned using two fluidsare cold fluid (water) in tempratur (Tco = 37 ° C) with a flow rate past the fluid (mc = 0.122 kg / s)and the hot fluid (oil) on tempratur (Thi = 47 ° C) with a flow rate past the fluid (mh = 0.075 kg /s) in which the operation of Heat exchanger will be operated on a thermal load constant that isequal to 5100 watts, then in in the planning of found the number of tube of Heat exchanger was 37pieces with effectiveness of Heat exchanger result of the design is 62%.